Immunomodulatory indications of azithromycin in respiratory disease: a concise review for the clinician. Issue 5 (4th July 2017) - Cramer, Cassondra L.; Patterson, Allie; Alchakaki, Abdulrazak; Soubani, Ayman O.
ABSTRACT: Azithromycin has a well-characterized bacteriostatic activity. However, it also has a robust immunomodulatory effect that has proven beneficial in a variety of chronic illnesses. This effect results in decreased production of pro-inflammatory cytokines in the acute phase and promotes resolution of chronic inflammation in the later phases. Specifically, azithromycin has direct activity on airway epithelial cells to maintain their function and reduce mucus secretion. These characteristics have resulted in the use of azithromycin in the management of a variety of chronic lung diseases including chronic obstructive pulmonary disease, cystic fibrosis (CF), non-CF bronchiectasis, bronchiolitis obliterans syndrome, diffuse panbronchiolitis, and asthma. In this review, we present the evidence supporting the role of azithromycin in these conditions with an emphasis on the clinical aspects for the practicing physician.